If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -10 = 2x + -2 Reorder the terms: -10 + 8x = 2x + -2 Reorder the terms: -10 + 8x = -2 + 2x Solving -10 + 8x = -2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 8x + -2x = -2 + 2x + -2x Combine like terms: 8x + -2x = 6x -10 + 6x = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 6x = -2 + 0 -10 + 6x = -2 Add '10' to each side of the equation. -10 + 10 + 6x = -2 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = -2 + 10 6x = -2 + 10 Combine like terms: -2 + 10 = 8 6x = 8 Divide each side by '6'. x = 1.333333333 Simplifying x = 1.333333333
| 7x^2+38x+15x= | | 7x-(5x-2)=10 | | 3b+1=5 | | 11=7x-1 | | 5x-27=3 | | -4v+3(w+2v)-5w= | | x^2-x+8100=0 | | 7z-7=0 | | 4x^2+15xy+9y^2= | | 3*(c+8)=48 | | -81x^3+x^2=0 | | 3*c+8=-48 | | 3x-7=3(x+3) | | 8*p=64 | | -25x^3+5x^2=0 | | 0.30x+.05(18-x)=.10(54) | | 3y-10-11y-6=-4y-13 | | 5(3x+3+4x-2-5x)=4x+17 | | 8m+13=+8m | | 2(X-4)-2(6X+1)=0 | | 2x-12=-4(2x-2) | | 2[x-2x-8+3]=2x+10 | | x^2+7x+73=0 | | X^2-20=2+x | | (4x-46)-6x=2x-10 | | 10x^2+19xy+6y^2= | | x^2-12x+1=3 | | 4.8q-3.7-5.9q=-0.1q-3.7 | | 3n+-3=n-5 | | 5x+8-12x=16-15x | | 4z=5z | | 2.7x-0.8-0.7x=-2x+2(4x+0.2) |